Performance of Existing Pediatric Early Warning System (PEWS) at Sikhoraphum Hospital - Sutthithumthaworn, Amphairat (Srinagarind Medical Journal, 2023)
Background and Objective: Pediatric patients are more likely to have unplanned crises. Identifying critically at-risk pediatric patients at the time of arrival will help them receive timely and appropriate care. This study aimed to determine the effectiveness of the pediatric early warning system (PEWS) of Sikhoraphum hospital. Method: A retrospective cohort study was conducted. The sample consisted of patients aged over 1 month to 15 years, and whose medical records were all assessed with the PEWS systems between January to December 2021. The instruments was PEWs record forms, and the content validity index was at 1.00. Data were assessed using diagnostic tests as sensitivity, specificity and discrimination areas under the ROC curve (AROC). Result: A total of 123 children were included for analysis. The mean age was 4.4 years (standard deviation, SD = 4.24). The cut-off point for PEWS score above 2 points; to predict the need for admission with a sensitivity of 73.17 %, specificity of 46.34 % and AROC for predicting admission were 66.11 % (95%CI 0.5609-0.7611); to predict the need for PICU admission with a sensitivity of 95.56 %, specificity of 50.00 % and AROC for predicting PICU admission were 85.36 % (95%CI 0.7846-0.9224); to predict the need for refer with a sensitivity of 80.77 %, specificity of 37.11% and AROC for predicting refer were 64.85 % (95%CI 0.5315-0.7654) Conclusion: It is recommended that PEWS is a good predictor at risk for PICU admission, which can help with diagnosis and catching symptoms prior to deterioration in order to improve the efficiency and effectiveness of patient care.